Kontribusi Motivasi Kerja, Komunikasi Interpersonal dan Supervisi Instruksional Terhadap Keterampilan Guru Mengelola Pembelajaran Bidang Studi Bahasa Arab (Studi pada MA/MTs Negeri dan Swasta se-Kota Padangsidimpuan) - Pane, Akhiril (AIN Padangsidimpuan, 2014)
This research intent to know variable contribution motivates job,Â interpersonal's communication and instruksional's supervision to Â Â skill learns to bring off learning. This research is executed on MA/ MTs Country and Swasta one Padangsidimpuan's City by totals sample 45 teachers. Its data collecting doing to utilize kuesioner to variable fourth. Fourth examination result this research hypothesis points out to mark sense relationship and konstribusi is variable is free good alone and also together to bonded variable be signifikan